An Overview of Factors Associated with the Incidence of Stunting - Witdiawati Witdiawati; Adelse Prima Mulya; Salsa Aisyah (Indonesian Journal of Global Health Research, 2025)
Stunting is one of the prevalent public health issues in society, affecting the quality of life of children under five and the nation's future productivity. Objective: This study aims to describe the factors associated with stunting among children under five in Sukamentri Village, under the jurisdiction of Guntur Public Health Center, Garut City. Method: This research employs a descriptive quantitative design with a cross-sectional approach. The study sample comprises 26 stunted children aged 0–59 months and their parents from 21 families in Sukamentri Village, selected using total sampling. The research was conducted from August to September. Data analysis includes univariate analysis with frequency distribution. Results: The findings reveal that the majority of stunted children are female (57.69%) and aged 0–36 months (65.38%). Most mothers of stunted children have a high school education level (38.10%), monthly income exceeding the UMK Garut Regency (76.19%), and access to health insurance, predominantly BPJS (85.71%). Regarding sanitation facilities, almost all families have private toilets (95.24%), dispose of feces in drains (57.14%), and discharge wastewater into rivers or drains (85.71%). Immunization among stunted children is incomplete (53.85%), most attend integrated health posts (73.08%), and consume snacks 1–2 times daily (69.23%), with 80.77% being packaged foods. Conclusions: These findings highlight the need for multidimensional interventions to reduce stunting prevalence, including nutrition education, sanitation improvement, and strengthening family economic resilience. A holistic approach involving cross-sectoral collaboration is necessary to create a supportive environment for optimal child growth and significantly reduce stunting prevalence.